Protection of Personal Data Against Doxing in Online Streaming Platforms - Seto Nugroho, Fajar; Ningtyas, Mega Ayu; Muljono, Bambang Eko; Hidayatullah, Ferdiansyah Safi’i (Jurnal Independent, 2026)
The rapid development of technology and information today has given rise to new crimes, one of which is doxing on online streaming platforms. Doxing has become a serious threat due to the rapid exchange of information today. Based on the above background, the author would like to propose a problem formulation, namely, first, what are the legal regulations for protecting personal data on online streaming platforms? And second, what are the legal sanctions for doxing perpetrators on online streaming platforms? In this study, a normative juridical research method was used with a statutory and conceptual approach. With primary legal materials. From the research results it can be concluded that: first, the legal rules for protecting personal data in online streaming platforms are that online streaming platforms that process and control personal data must be in accordance with the objectives, obtain the consent of the person concerned, be transparent, have adequate security and protect against unauthorized access or distribution in accordance with articles 16 to 39, related regulations also exist in the processing of personal data carried out by protecting the security of personal data from loss, misuse, access and unauthorized disclosure in accordance with Government Regulation Number 71 of 2019 concerning the implementation of electronic systems and transactions, article 14 paragraph (1) letter (e) And secondly, the legal sanctions for doxing perpetrators in online streaming platforms can be punished with a maximum of 4 years in prison and a maximum fine of 4,000,000,000 (four billion rupiah), in accordance with Article 67 paragraph (2) of Law Number 27 of 2022 concerning the protection of personal data, in carrying out doxing the perpetrator must also collect the personal data of the victim, this has violated Law Number 27 of 2022 concerning the protection of personal data including Article 67 paragraph (1) carries a maximum prison sentence of 5 years and a maximum fine of 5,000,000,000 (five billion rupiah).